Can luxury and environmental sustainability co-exist? Assessing the environmental impact of resort tourism on coral reefs in the Maldives - Cowburn, Benjamin; Moritz, Charlotte; Birrell, Chico; Grimsditch, Gabriel; Abdulla, Ameer (Ocean & coastal management, 2018)
Tourism is a mainstay of the Maldivian economy, with approximately 1 million tourists a year attracted by the rich tropical marine ecosystems and the luxurious service and experience offered in the country's resorts. However, developing and running resorts to cater for tourists on relatively small and remote islands presents various environmental challenges for surrounding coral reefs. We investigated the potential impacts of tourism operations, including construction, sewage, pollution and sand pumping, on reef condition around seven islands exclusively leased for resorts. We reported variable environmental sustainability of resort practices, with some in particular being damaging. The initial construction of the resort represented an acute impact on reef condition, inferred from the lower coral cover and lower abundance of large and mature coral colonies around the newest resorts investigated. Levels of algal cover and loose sediment were higher on reef sites near the resorts, where the majority of the damaging activities take place. However, resorts activities were less important for explaining reef condition than the differences between habitats, such as the reef flat or slope, and the atoll where the resort was located. Compared to other regions globally, tourist development appeared to have less impact on reef condition in the Maldives maintaining moderately high coral cover and features of a resilient ecosystem. It is important to note that better waste management and the use of environmentally friendly infrastructure development is needed to reduce the impacts of resorts in the Maldives. •Maldivian resorts operate in close proximity to fragile coral reef habitats.•Potentially damaging impacts include sewage, pollution and construction.•Reefs closer to resorts had more algae and loose sediment covering the benthos.•Construction seems to kill corals, indicated by a lack of big corals near new resorts.•Environmental sustainability is desirable for resorts, but not easy to achieve.